PERAN KEPEMIMPINAN TOKOH INFORMAL TERHADAP KEMANDIRIAN KELOMPOK TANI HUTAN - Suyadi Suyadi; Dyah Ekaprasetya MR (Program Studi Pengembangan Masyarakat Islam (PMI) FIDIKOM, UIN Syarif Hidayatullah Jakarta, 2020)
AbstractCommunities that exist around the forest in general are still very dependent on their leaders. Effectiveness empowerment of forest communities/reserves can be measured from three aspects of self-reliance in the economic, social, cultural and ecological. The purpose of this study are: (1) analyze the effect of a leadership role informal leader of the economic self-reliance of forest farmer groups in the village of Kopo District Cisarua Bogor, (2) analyze the effect of a leadership role informal leader of the self-reliance of the ecology of forest farmer groups in the village of Kopo District Cisarua Bogor, (3) analyze the effect of the leadership role the informal leaders of the social and cultural independence of forest farmer groups in the village of Kopo District Cisarua Bogor. The research was conducted from March to May 2016. Data were analyzed using multiple regression analysis. The conclusions of this study are (1) a leadership role informal leaders did not significantly affect the economic self-reliance of forest farmer groups in the village of Kopo District Cisarua Bogor, (2) a leadership role as informal community leaders (the informational role) significantly affected the self-reliance of the ecology of forest farmer groups in the village of Kopo District Cisarua, Bogor, (3) the leadership role of informal leaders did not significantly affect social and cultural self-reliance of forest farmer groups in the village of Kopo District Cisarua, Bogor.Keywords: leadership; informal; self-relianceAbstrakMasyarakat yang ada di sekitar hutan pada umumnya masih sangat tergantung pada pemimpin mereka. Efektifitas pemberdayaan masyarakat sekitar kawasan konservasi dapat diukur dari kemandirian masyarakat dalam tiga aspek ekonomi, sosial budaya dan ekologi. Tujuan penelitian ini yaitu: (1) menganalisis pengaruh peran kepemimpinan tokoh informal terhadap kemandirian ekonomi kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor, (2) menganalisis pengaruh peran kepemimpinan tokoh informal terhadap kemandirian ekologi kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor, (3) menganalisis pengaruh peran kepemimpinan tokoh informal terhadap kemandirian sosial budaya kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor. Penelitian dilaksanakan bulan Maret sampai Mei 2016. Data yang diperoleh dianalisis menggunakan analisis regresi berganda. Kesimpulan penelitian ini adalah (1) peran kepemimpinan tokoh informal tidak berpengaruh nyata terhadap kemandirian ekonomi kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor, (2) peran kepemimpinan tokoh informal (peran informasional) berpengaruh nyata terhadap kemandirian ekologi kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor, (3) peran kepemimpinan tokoh informal tidak berpengaruh nyata terhadap kemandirian sosial budaya kelompok tani hutan di Desa Kopo Kecamatan Cisarua Kabupaten Bogor.Kata kunci: kepemimpinan; informal; kemandirian